1994
DOI: 10.3904/kjim.1994.9.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Interphase Cytogenetics of Lung Tumors Using In Situ Hybridization: Numerical Aberrations

Abstract: ObjectivesSince conventional cytogenetic analysis for bronchogenic carcinogenesis is limited by the difficulty to get enough number of high quality metaphase spreads, the development of new method to overcome above problems is strongly needed. Therefore, the introduction of non-radioactive in situ hybridization (ISH) with pericentromeric chromosome probes gave us the way to investigate the genetic events during carcinogenic process. We applied this method on lung cancer tissue to validate the possibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…CGH and FISH studies of resected lung carcinoma tissue have shown that non–small cell and small cell lung carcinoma are characterized by widespread gains (low‐level and high‐level) and losses of genetic material at various chromosomal loci 20, 21, 27, 41–45. This has led a few investigators to use FISH to assess sputum or bronchoscopically obtained specimens for evidence of lung carcinoma cells 6, 37, 46, 47…”
Section: Discussionmentioning
confidence: 99%
“…CGH and FISH studies of resected lung carcinoma tissue have shown that non–small cell and small cell lung carcinoma are characterized by widespread gains (low‐level and high‐level) and losses of genetic material at various chromosomal loci 20, 21, 27, 41–45. This has led a few investigators to use FISH to assess sputum or bronchoscopically obtained specimens for evidence of lung carcinoma cells 6, 37, 46, 47…”
Section: Discussionmentioning
confidence: 99%